2022
DOI: 10.1007/s10787-022-01002-1
|View full text |Cite
|
Sign up to set email alerts
|

The key role of Calpain in COVID-19 as a therapeutic strategy

Abstract: COVID-19 is one of the viral diseases that has caused many deaths and financial losses to humans. Using the available information, this virus appears to activate the host cell-death mechanism through Calpain activation. Calpain inhibition can stop its downstream cascade reactions that cause cell death. Given the main roles of Calpain in the entry and pathogenicity of the SARS-CoV-2, its inhibition can be effective in controlling the COVID-19. This review describes how the virus activates Calpain by altering ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Under normal conditions, autophagy suppresses inflammatory factors, but defective autophagy seen in SARS-CoV-2 reveals that the virus and viral-altered processes may uncontrollably stimulate inflammatory pathways [67,79,95]. One example is that ROS accumulation stimulates various mechanisms of inflammation, including inflammasomes and calpain, to produce IL-1B and IL-1a, respectively [96][97][98]. They also increase RIG-I-like receptors to enhance type-I IFN production.…”
Section: Autophagy and The Replication Of Sars-cov-2mentioning
confidence: 99%
“…Under normal conditions, autophagy suppresses inflammatory factors, but defective autophagy seen in SARS-CoV-2 reveals that the virus and viral-altered processes may uncontrollably stimulate inflammatory pathways [67,79,95]. One example is that ROS accumulation stimulates various mechanisms of inflammation, including inflammasomes and calpain, to produce IL-1B and IL-1a, respectively [96][97][98]. They also increase RIG-I-like receptors to enhance type-I IFN production.…”
Section: Autophagy and The Replication Of Sars-cov-2mentioning
confidence: 99%
“… 15 , 16 Although the detailed mechanism is unknown, evidence suggested that calpains, another class of intracellular calcium-activated cysteine proteases, also play a key role in the early steps of the coronaviral life cycle. 17 , 18 As such, both proteases are potential targets for broad-spectrum antiviral intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several reports on the effective coronavirus inhibitors that target host CTSL and/or CAPN1 (Supplementary Scheme S1). 17,[28][29][30] Most of them were identified through drug repurposing efforts. Several promising repurposed drugs are undergoing clinical trials for the treatment of COVID-19, e.g., CTSL inhibitor SLV213 (https:// clinicaltrials.gov/ct2/show/NCT04843787), which was originally developed as a therapeutic for the treatment of Chagas disease, 31 and calpains inhibitor BLD2660 (https://clinicaltrials.gov/ct2/show/ results/NCT04334460), which was originally developed for the treatment of fibrotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Current knowledge suggests that calpain 1 may play a dual role in the development of ARDS: a direct cytopathic effect and an increase in the inflammatory response through direct activation of IL-33, which contributes to the development of cytokine storm and ARDS. In addition, the role of calpain 1 has also been described in terms of the internalization of the virus into cells, and its inhibitors are placed in the context of potential drugs for the treatment of COVID-19 [30,31].…”
Section: Introductionmentioning
confidence: 99%